Shaping of the systems of greenery in the districts of Lublin Cooperative Housing (LSM) in the context of planning and implementation of the project - Boguszewska, Kamila; Przesmycka, Natalia (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2018)
Collective Housing districts of Lublin Cooperative Housing (LSM) were the example of model multifamily developments of the second half of the twentieth century, conceptually designed by Roman Dylewski (architect and urban planner) in the years 1956−1977. They were built in the southern part of the city, on the hills cut by dry valleys and ravines, which significantly influenced the form of the buildings and the way of shaping the architectural and landscape enclosures. The Housing district named after polish poet Adam Mickiewicz, designed by Felix Haczewski was based on the garden city concept. Famous visionary architect Oskar Hansen implemented his idea of a linear system and the principle of “absorbent background” into design of Juliusz Słowacki`s district. LSM housing districts were planned in detail, starting from the urban plan of the entire area, through architecture and meticulous arrangement of public spaces. Particular emphasis has been put on the nature of public and social activity spaces, as well as the surrounding greenery. Various species of trees, shrubs and perennials were planted as a complementary element of social space in the district, which was also a part of the city’s greenery system. Different elements of small architecture, such as: sculptures, ponds, and “rockeries” were placed there. The article aims to characterize the principles of landscape and greenery design, as an inseparable element of LSM district and its current condition. It is also interesting to study the transformation of the city sections deriving not only from the changing needs of users, but also from aesthetic preferences and the desire to follow a widely understood design trends.